Fusion of EML4 and ALK is associated with development of lung adenocarcinomas lacking EGFR and KRAS mutations and is correlated with ALK expression - Zhang, Xuchao (BioMed Central, 2010)
BACKGROUND: The anaplastic lymphoma kinase (ALK) gene is frequently involved in translocations that lead to gene fusions in a variety of human malignancies, including lymphoma and lung cancer. Fusion partners of ALK include NPM, EML4, TPM3, ATIC, TFG, CARS, and CLTC. Characterization of ALK fusion patterns and their resulting clinicopathological profiles could be of great benefit in better understanding the biology of lung cancer. RESULTS: RACE-coupled PCR sequencing was used to assess ALK fusions in a cohort of 103 non-small cell lung carcinoma (NSCLC) patients. Within this cohort, the EML4-ALK fusion gene was identified in 12 tumors (11.6%). Further analysis revealed that EML4-ALK was present at a frequency of 16.13% (10/62) in patients with adenocarcinomas, 19.23% (10/52) in never-smokers, and 42.80% (9/21) in patients with adenocarcinomas lacking EGFR and KRAS mutations. The EML4-ALK fusion was associated with non-smokers (P = 0.03), younger age of onset (P = 0.03), and adenocarcinomas without EGFR/KRAS mutations (P = 0.04). A trend towards improved survival was observed for patients with the EML4-ALK fusion, although it was not statistically significant (P = 0.20). Concurrent deletion in EGFR exon 19 and fusion of EML4-ALK was identified for the first time in a Chinese female patient with an adenocarcinoma. Analysis of ALK expression revealed that ALK mRNA levels were higher in tumors positive for the EML-ALK fusion than in negative tumors (normalized intensity of 21.99 vs. 0.45, respectively; P = 0.0018). However, expression of EML4 did not differ between the groups. CONCLUSIONS: The EML4-ALK fusion gene was present at a high frequency in Chinese NSCLC patients, particularly in those with adenocarcinomas lacking EGFR/KRAS mutations. The EML4-ALK fusion appears to be tightly associated with ALK mRNA expression levels. RACE-coupled PCR sequencing is a highly sensitive method that could be used clinically for the identification of EML4-ALK-positive patients.